The Augmented Reality Application for Waruga Cultural Heritage Recognition: Aplikasi Augmented Reality Pengenalan Cagar Budaya Waruga - Meilani Rosinta Emma Angouw; Oktavian Lantang; Virginia Tulenan (Jurnal Teknik Informatika, 2023)
Abstract  —  Waruga is one of the cultural heritages which is the ancestral tomb of the Minahasa tribe which is made of sedimentary rock called tufa, the local language is called apela/domato. The lack of easily accessible information and the lack of interest in the information presented has resulted in a decrease in interest in getting to know the waruga cultural heritage. Augmented reality technology offers great potential in enriching the user experience and facilitating understanding of waruga. This study uses the image target tracking method so that target detection is based on images. For the development method using the multimedia development life cycle which has 6 stages and produces an application augmented reality introduction to the waruga cultural heritage which includes 13 markers and 12 3D objects. Based on the test results involving 31 respondents in a questionnaire with 10 questions regarding understanding of waruga cultural heritage, the average answer was 94.19 out of 100 points with a range of 70-100 points. By employing augmented reality technology, we can develop an application for recognizing the cultural heritage of Waruga. Key words— Augmented reality, Cultural Heritage, Image target, Waruga   Abstrak — Waruga adalah salah satu cagar budaya yang merupakan makam leluhur suku Minahasa yang terbuat dari batuan sedimen yang bernama tufa, bahasa daerahnya disebut apela/domato. Kurangnya informasi yang mudah diakses serta kurang menariknya informasi yang disajikan menyebabkan menurunnya minat untuk mengenal cagar budaya waruga. Teknologi augmented reality menawarkan potensi yang besar dalam memperkaya pengalaman pengguna dan memfasilitasi pemahaman tentang waruga. Penelitian ini menggunakan metode pelacakan image target sehingga pendeteksian target berdasarkan gambar. Untuk metode pengembangan menggunakan multimedia development life cycle yang memiliki 6 tahap dan menghasilkan aplikasi augmented reality pengenalan cagar budaya waruga yang meliputi 13 marker dan 12 objek 3D. Berdasarkan hasil pengujian yang melibatkan 31 responden pada kusioner dengan 10 pertanyaan mengenai pemahaman tentang cagar budaya waruga, didapatkan rata-rata jawaban 94,19 dari 100 poin dengan rentang 70-100 poin. Sehingga dengan menerapkan teknologi augmented reality didapatkan suatu aplikasi pengenalan cagar budaya waruga. Kata kunci — Augmented reality, Cagar Budaya, Image target, Waruga